PENINGKATAN KREATIVITAS DAN HASIL BELAJAR KIMIA POKOK BAHASAN MATERI SISTEM KOLOID DENGAN MODEL BAKULIKAN DI KELAS XII SEMESTER 2 SMA NEGERI 1 PAPALANG KABUPATEN MAMUJU - Faisal Akib (PINISI :Journal of Teacher Professional, 2021)
Students of SMA Negeri 1 Papalang, Mamuju Regency, especially class XII, only achieved mastery in chemistry at 46.51% in the block I test. So the purpose of this class action research is to find out the increase in learning outcomes and creativity of SMA Negeri 1 Papalang Mamuju Regency after using the Bakulikan model (Read, Discuss, See and Do). The Baculikan model is a learning model that combines 4 activity patterns, namely reading, discussing, seeing and doing. This research is a classroom action research consisting of 3 cycles. Each cycle includes planning, action, observation and reflection activities. The focus in this research is the learning outcomes and creativity of class XII students at SMA Negeri 1 Papalang, Mamuju Regency for the 2020/2021 academic year. Data collection techniques in this study were observation, end-of-cycle tests and questionnaires. Based on the analysis of research data, the average student learning outcomes in cycle I was 73.56, in cycle II was 74.89 and in cycle III was 81.55. So that the percentage of mastery learning outcomes in cycle I was 79.07%, in cycle II it rose to 86.05% and in cycle III it increased again to 95.35%. While the creativity of students also increased, namely 51.72% in cycle I rose to 60.56% in cycle II and increased again in cycle III to 70.14%. Based on the discussion of the results of this study, it was concluded that the Baculikan model can improve student learning outcomes and creativity. The suggestion put forward is that the Baculikan model can be used by teachers in learning.